ALIENATED WORK AND NATURE PRECARIZATION AND DEGRADATION OF WORK AND NATURE - Machado, Angela dos Santos [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2019)
Does our specificity as human beings, producers of culture, of work, and of a second nature make us external or superior to the rest of nature? We defend the idea of nature as totality, but without ignoring this human specificity and understanding work as the intermediation between the first and second nature (understood as a totality). We discuss the conceptions of nature, searching for their bases in philosophy, passing through modern science and punctuating their understanding in different periods within geography. Finally, we wonder if work is the intermediation between the social and the natural, and this work is increasingly alienated, how does this imply in our conception of nature? More than that, we aim to understand how precarization extrapolates the world of work and leads to the degradation of nature as a whole.
Keywords: Nature; Society; Job; Precariousness; Degradation